Comprehensive somatosensory and neurological phenotyping of NCS1 knockout mice - Lien D. Nguyen (Scientific Reports, 2021)
Abstract Neuronal calcium sensor 1 (NCS1) regulates a wide range of cellular functions throughout the mammalian nervous systems. Altered NCS1 expression is associated with neurodevelopmental and neurodegenerative diseases. Previous studies focused on affective and cognitive behaviors in NCS1 knockout (KO) mice, but little is known about the physiological and pathological states associated with the loss of NCS1 in the peripheral nervous system. We previously reported that NCS1 expression was reduced following paclitaxel-induced peripheral neuropathy. Here, we comprehensively investigated the phenotypes of NCS1-KO mice through a battery of behavioral tests examining both central and peripheral nervous systems. Generally, only mild differences were observed in thermal sensation and memory acquisition between NCS1-WT and -KO male mice, but not in female mice. No differences were observed in motor performance, affective behaviors, and hearing in both sexes. These results suggest that NCS1 plays a modulatory role in sensory perceptions and cognition, particularly in male mice. NCS1 has been proposed as a pharmacological target for various diseases. Therefore, the sex-specific effects of NCS1 loss may be of clinical interest. As we examined a constitutive KO model, future studies focusing on various conditional KO models will further elucidate the precise physiological significance of NCS1.